The connection of ellipsoidal and normal heights when applying the collocation method - Skeivalas, Jonas; Stankevičius, Žilvinas (Geodesy and Cartography, 2012)
The prognostic normal heights models compiled by the collocation method are analysed in the article. The elipsoidic heights determined by GPS measurements are used for this case. Systems of equations are applied for prognostic modelling applying polynoms of a relevant order. The parameters of the optimal prognostic model are obtained according to statistical declinations of elipsoidic and normal heights at identical points. This is performed by changing the sequence of the polynoms and the elements of matrix of weights at elipsoidic and normal heights. The formulas for evalution of the influence of the elipsoidic heights errors for the accuracy of the parameters of prognostic model are presented.Article in Lithuanian.Elipsoidinių ir normalinių aukščių sąsaja, taikant kolokacijos metodąSantrauka. Straipsnyje analizuojami normalinių aukščių prognozės modeliai, sudaryti kolokacijos metodu, įtraukiant GPS matavimais nustatytus elipsoidinius aukščius. Prognozės modeliams sudaryti išvedamos lygčių sistemos, taikant atitinkamos eilės daugianarius. Optimalaus prognozės modelio parametrų reikšmės gaunamos pagal statistinius elipsoidinių ir normalinių aukščių nuokrypius identiškuose taškuose, keičiant daugianarių eilę ir elipsoidinių bei normalinių aukščių svorių matricos elementus. Pateikiamos formulės elipsoidinių aukščių klaidų įtakai prognozės modelio parametrų bei normalinių aukščių tikslumui įvertinti.Raktažodžiai: elipsoidiniai ir normaliniai aukščiai, prognozavimas, kolokacija, kovariacija, GPS, geoidas.First published online: 03 Aug 2012